Two to tango: regulation of mammalian iron metabolism - Hentze, Matthias W.; Muckenthaler, Martina; Galy, Bruno; Camaschella, Clara (Cell, 2010)
Disruptions in iron homeostasis from both iron deficiency and overload account for some of the most common human diseases. Iron metabolism is balanced by two regulatory systems, one that functions systemically and relies on the hormone hepcidin and the iron exporter ferroportin, and another that predominantly controls cellular iron metabolism through iron-regulatory proteins that bind iron-responsive elements in regulated messenger RNAs. We describe how the two distinct systems function and how they “tango” together in a coordinated manner. We also highlight some of the current questions in mammalian iron metabolism and discuss therapeutic opportunities arising from a better understanding of the underlying biological principles.
Gesehen am 19.042023